Morphoanatomical characterization of Brassavola tuberculata Hook´s (Orchidaceae) leaf and root upon the rocky outcrop - Silva, Fernanda Maria Trindade da; Barbosa, Wellington Marota; Ferreira-Júnior, Walnir Gomes (Revista Agrogeoambiental, 2022)
Orchids have morphological and anatomical adaptations that make them able to occupy the most different environments with the most varied conditions. These adaptations, together with the physiological attributes are essential for the establishment, growth, reproduction, and colonization of orchids. Therefore, this study was developed to describe the leaf and root anatomy of Brassavola tuberculata Hook found in a phorophyte located on a rocky outcrop in Campestre, southern Minas Gerais. The collected leaf and root samples were freehand cut and stained with astra blue and safranin. The histochemical tests applied wer: sudan III for lipids and lugol for starch. The leaves are subulate, succulent and grooved containing a continuous longitudinal cannula. The epidermis has a thick cuticle, stomata with a suprastomatal chamber on both leaf faces and the mesophyll is homogeneous with aquifer parenchyma in the central portion. In the root, the velamen and cortical tissue are composed of several cell layers that allow it to store water. There were starch grains in the leaf and root. These xeromorphic characters found allow to the species to survive in the restricted conditions found in the phorophyte on rocky outcrops.